(untitled) (International Seven Journal of Health Research, 2025)
Introduction: Sexuality is determined by multiple factors. The knowledge and perceptions of the individual’s environment will determine their behavior in this regard. Identifying the perceptions in a population that attends higher education is important to carry out specific prevention activities, since the repercussions of their sexual behavior are decisive for the public health of populations. Objective: Determine what are the perceptions and the main sexual risk behaviors in American university students. Method: Systematic review. The search was carried out in the Cochrane, Medigraphic and PubMed databases with the search words sexual behavior, college students, finding 25,821 results, filtered by language (English or Spanish), access to full text, year of publication (2016- 2021), geographic area (American continent) and sample (university population), resulting in n=12 articles. Results: most of the authors agree that American university students, despite having knowledge regarding sexuality and Sexually Transmitted Infections (STIs), do not carry out preventive actions, with a beginning of sexual life approximately at the age of fifteen and multiple partners. simultaneous; condom use is predominant as a method of family planning and sexting as a risky sexual behavior has become more important in recent years. Conclusions: the high prevalence of risk behaviors and the low use of diagnostic tests supports the fact that America is one of the continents with the most annual diagnoses of STIs in the world, with consequences that can be of varying severity and even fatal.